Wireless Modular Implantable Neural Device with One‐touch Magnetic Assembly for Versatile Neuromodulation - Inho Kang; John Bilbily; Choong Yeon Kim; Chuanqian Shi; Manish K. Madasu; Eun Young Jeong; Kyle E. Parker; Do A Kwon; Bum‐Joon Jung; Jae‐Soon Yang; Juhyun Lee; Noah D.L. Kabbaj; et al. (Advanced Science)
Abstract Multimodal neural interfaces open new opportunities in brain research by enabling more sophisticated and systematic neural circuit dissection. Integrating complementary features across distinct functional domains, these multifunctional neural probes have greatly advanced the interrogation of complex neural circuitry. However, introducing multiple functionalities into a compact form factor for freely behaving animals presents substantial design hurdles that complicate the device or require more than one device. Moreover, fixed functionality poses challenges in meeting the dynamic needs of chronic neuroscience inquiry, such as replacing consumable parts like batteries or drugs. To address these limitations, the modular implantable neural device (MIND) is introduced with a one‐touch magnetic assembly mechanism. Leveraging the seamless exchange of neural interface modules such as optical stimulation, drug delivery, and electrical stimulation, MIND ensures functional adaptability, reusability, and scalability. The versatile design of MIND will facilitate brain research by enabling simplified access to multiple functional modalities as needed.